Autonomic nervous system coordination moderates links of interparental conflict with adolescent externalizing behaviors - McKernan, Charlotte J., author; Lucas-Thompson, Rachel G., advisor; Shomaker, Lauren, committee member; Rosen, Lee, committee member (Colorado State University. Libraries, 2017)
Although negative interparental conflict predicts elevated externalizing problems for children, there are individual differences in this association. Theoretically, children's abilities to coordinate physiological stress across response systems moderate the effects of interparental conflict on outcomes. Past research has demonstrated that poor coordination of sympathetic (SNS) and parasympathetic (PNS) nervous systems puts children at a greater risk for externalizing behaviors in the context of interparental conflict. The goal of this study was to whether this same pattern is evident in adolescents. Participants were families with an adolescent (10-17 years) from diverse ethnic and socioeconomic backgrounds. Parents reported conflict, were observed during a conflict discussion, and reported adolescent externalizing behaviors. Adolescents experienced a stressor while skin conductance (SC; SNS) and respiratory sinus arrhythmia (RSA; PNS) were measured. Similar to past research with children, there were three-way interactions between negative, threatening interparental conflict, SC-R, and RSA-R in relation to adolescent externalizing behaviors. Adolescents who displayed poorly coordinated responding displayed a positive association between interparental conflict and externalizing behaviors, whereas adolescents who showed well-coordinated responding displayed a negative association between conflict dimensions and externalizing behaviors. Results indicate that SNS and PNS coordination may protect adolescents from experiencing increased externalizing behaviors in the context of interparental conflict.